Faces do agir docente em projetos cooperativos de internacionalização: uma leitura interacionista sociodiscursiva de representações sobre políticas de idiomas estrangeiros no contexto dos Institutos Federais - Cavalcante, Rivadavia Porto (2016)
This thesis performs a study with two language teachers (Portuguese and English) teachers who are engaged in internationalization cooperative projects of the Federal Institutes of Education. Science and Technology (IFs).The main goal was to investigate representations constructed by such teachers who act in favor of a specific language policy implementation in order to develop language practices according to those institutions specific programs. This study is motivated by the fact that, when it comes to language policies implementation context, teachers also act as international advisors in their respective institutions. They recontextualize (interpret and recreate) policies.To achieve the thesis purposes, I adopted a discursive analysis of written texts, that is, documents produced collectively, with the participation of these educators. Besides, I analyzed semi-structured interviews done with the collaborators to understand their activities progress in social background of surveyed institutions. Data analysis were based on Sociodiscursive Interactionism (ISD) theoretical and methodological contributions, which prioritize praxis phenomenon in texts-discourse analysis. Considering the object particularities under investigation, I established a coupling between the ISD assumptions (BRONCKART, 1999, 2008b; BULEA, 2014a), the conceptual contributions of Applied Linguistics and Language Policies (SPOLSKY, 2009, 2004; SHOHAMY, 2006, 2009; MENKEN and GARCIA, 2010; HÉLOT, 2014) and Education Sociology theories (BALL et. Al., 1992, 1993, 1994, BALL, 2006).These additional contributions prioritize in their approaches, practices as the strongest element in the definition of a policy. Such complementary contributions also approach contextualized practices as the strongest element in defining a policy. Methodology proceedings was guided by text analysis updated model proposed by Bronckart (2008a, 2008b, 2010a), Bulea & Bronckart (2008) and Bulea (2010, 2014b), along with interpretative hermeneutics contributions by Rastier (1998, 2001a, 2009). About data analysis, written and oral texts were considered as a starting point. At first, I measured aspects of socio-political and cultural universe related to the historical moment that influenced conditions/situations correlated to production and reception conditions, followed by its internal structural and functional properties. Study results revealed that the two Advisor Teachers, when confronted with State inadequate public educational policies in their institutional contexts, built knowledge embodied to implementation of alternative proposal for language policy represented in their “Projetos de Centro de Idiomas” (PCI, Language Center Projects), such as fostering international action designed to such institutions. Data evidence the social, active and decisive role performed by Advisor Teachers to formulate and implement Language Policies. When the teachers adapt those policies to institutional needs, their meanings were (re) defined according to teachers’ representations. PCI implementation process has reshaped goals and purposes of teaching and learning foreign languages in surveyed institutions. Innovative, cultural and collaborative practices were added in PCI, such as international partnerships, skill tests and cooperation of foreign trainees, among others, in order to integrate different languages to achieve academic mobility. Thus, representations and actions performed by Advisor Teachers have changed institutional standards, as well as the teaching staff and the training model proposed in terms of professional, scientific and technological formation driven by internationalization patters in this decade.